Accrediting Private Collections To Serve the Public Interest in Art - Toporoff, Andrew (The Columbia Journal of Law & the Arts, 2021)
This Note is about the civic role of private collections of art. Specifically, it argues that private collections can and should be a fixture of the U.S. cultural landscape alongside museums, which are devoted to serving the public. To some extent, this already happens. Collectors often lend their artwork for museum exhibitions, for example, and some put their entire collections up for public display. Nothing better illustrates the convergence of owning art as an asset and for conspicuous public display than one entrepreneur’s business idea to sell prefabricated private museums: Why not make it easy for collectors, with readymade galleries to accommodate the Koons or the Basquiat? But this Note adds to commentators who wish to see a reform in private collecting so that the public benefits more from these collections than it does currently. This Note argues that the public interest calls for enhancing, not subordinating, the role of private collectors. Certain commentators argue that collectors should be compelled to act in service to the public, either by lending significant works of art to a museum or publicly displaying the works themselves. Behind such proposals lies the notion that private collections and museums are in tension, and that museums are a superior institution for benefiting the public, if private collections are capable of providing public benefits at all. Informing this intuition are the legal and normative differences between private and museum ownership. Museums are subject to certain obligations that collectors do not share, the rationale for which is that they vindicate the public interest in art. But it does not follow from this distinction that collectors, lacking these obligations, cannot also promote the public interest through their own actions. Private collections should play a complementary role to museums in serving the public interest. Private collections and museum collections are qualitatively different in meaningful ways. Furthermore, museums appear increasingly unable to effectively promote the public interest in art, at least without help. Thus, this Note proposes a regime that would harmonize the civic practices of collectors and museums while preserving the role of the collector. Part I explains the differences between collectors and museums with respect to ownership. One way to understand these differences is to say that while collectors mostly operate under general principles of property law, their art being their chattel, museums are subject to certain obligations on account of their charitable status and purpose. Building on the idea that these obligations exist for the benefit of the public, Part II describes how previous scholars have defined the contours of the “public interest in art” and introduces one paradigm in particular for reforming private collecting so that it serves the public interest. Part II then critiques this paradigm and shows why a different approach is necessary; in doing so, it makes an important distinction between proposals that focus on individual works of art and proposals that focus on collections in their entirety. Part III outlines an incentive-based system for achieving the desired reform under this new approach. Accrediting private collections that meet certain criteria for providing public benefits could motivate collectors to act civically and promote better practices for private collecting broadly, depending on the benefits associated with accreditation.